A Stable π‐Conjugated Singlet Biradical. Issue 34 (27th June 2016) - Hinkel, Felix; Freudenberg, Jan; Bunz, Uwe H. F.
Abstract : A large polycyclic hydrocarbon with a singlet biradical ground state has been obtained by the combined effects of topology and electron‐accepting aromatic substituents, which stabilize its open‐shell singlet state.